Response to Krumreys Comments on Determination of X-ray flux using silicon pin diodes by R. L. Owen et al. (2009). J. Synchrotron Rad. 16, 143-153 - Owen, R; Holton, J; Schulze-Briese, C; Garman, E (2009)
A number of researchers published a paper in the Journal of Synchrotron Radiation that provided a basis for macromolecular crystallographers to determine the photon flux incident dose absorbed by a crystal during an experiment. The simple expression used by the researchers was derived directly from the geometry of the diode. The main aim of the paper was to determine the potential behavior of devices to be used in explained considering only primary absorption. The manufacturers' specifications and any deviation from these feeds directly through to the calculated flux were considered to obtain the fluxes. Another aim of the paper was to report a simple method to determine photon flux to an accuracy of 5 10% at MX beamlines using commercially available devices.